Bonum ex integra causa... A dialogue with Mieczysław Tomaszewski’s concept of integral interpretation - Jabłoński, Maciej (Interdisciplinary Studies in Musicology, 2018)
The article presents an in-depth and detailed reflection on the concept of „integral interpretation” put forward by the Polish musicologist Mieczysław Tomaszewski. The problematics of interpretation has for many years been the focus of Tomaszewski’s attention and interest, as evidenced by his numerous publications devoted to it. They culminate in the formulation of this concept, described by the author as the method of an adequate interpretation of a musical work. In contrast to many contemporary approaches to the issue of the scope of musicology’s subject area, for Tomaszewski the concept of a musical work is central to the discipline, and he poses questions concerning its ontology and understanding in the spirit of Roman Ingarden’s theory of musical work, to which he frequently refers. Tomaszewski regards the process of interpretation as a kind of „rising” to the level of the work, the meaning of which (intentio operis), often identified with the authorial meaning (intentio auctoris), stands at the highest point in the hierarchy of meanings ascribed - from this point of view - to the work. In turn, the work itself functions in different phases, existing as a score, a performance, a result of the processes of perception and as its reception within a culture. In my article I attempt not only to present Tomaszewski’s method, but above all to argue against its anachronicity and limitations resulting from a lack of reference both to contemporary artistic practice and contemporary research methodology in the humanities and in musicology.